Pedunculopontine network dysfunction in Parkinson's disease with postural control and sleep disorders. Issue 5 (6th February 2017) - Gallea, Cecile; Ewenczyk, Claire; Degos, Bertrand; Welter, Marie‐Laure; Grabli, David; Leu‐Semenescu, Smaranda; Valabregue, Romain; Berroir, Pierre; Yahia‐Cherif, Lydia; Bertasi, Eric; Fernandez‐Vidal, Sara; Bardinet, Eric; et al.
ABSTRACT: Background: The objective of this study was to investigate pedunculopontine nucleus network dysfunctions that mediate impaired postural control and sleep disorder in Parkinson's disease. Methods: We examined (1) Parkinson's disease patients with impaired postural control and rapid eye movement sleep behavior disorder (further abbreviated as sleep disorder), (2) Parkinson's disease patients with sleep disorder only, (3) Parkinson's disease patients with neither impaired postural control nor sleep disorder, and (4) healthy volunteers. We assessed postural control with clinical scores and biomechanical recordings during gait initiation. Participants had video polysomnography, daytime sleepiness self‐evaluation, and resting‐state functional MRIs. Results: Patients with impaired postural control and sleep disorder had longer duration of anticipatory postural adjustments during gait initiation and decreased functional connectivity between the pedunculopontine nucleus and the supplementary motor area in the locomotor network that correlated negatively with the duration of anticipatory postural adjustments. Both groups of patients with sleep disorder had decreased functional connectivity between the pedunculopontine nucleus and the anterior cingulate cortex in the arousal network that correlated with daytime sleepiness. The degree of dysfunction in the arousal network was related to the degree of connectivity in the locomotor network in all patients with sleep disorder, but not in patients without sleep disorder or healthy volunteers. Conclusions: These results shed light on the functional neuroanatomy of pedunculopontine nucleus networks supporting the clinical manifestation and the interdependence between sleep and postural control impairments in Parkinson's disease. © 2016 International Parkinson and Movement Disorder Society